Effective product-service systems: A value-based framework - Kuijken, Bram; Gemser, Gerda; Wijnberg, Nachoem M. (Industrial marketing management, 2017)
Manufacturers increasingly engage in servitization and as a result offer services in combination with their products (i.e., product-service systems, PSS). However, while servitization in theory seems to be a promising strategy, in practice, the bundling of services with product offerings does not always result in the expected performance outcomes. In this paper, we propose a framework that helps manufacturers to overcome this servitization paradox. The underlying premise of our framework is the need to give primacy to the value customers derive from PSS. The framework builds on the idea that products and services differ with regard to the value that is created by the tangible elements and the interaction moments between manufacturers and customers; this is presented in a 2×2 matrix. Subsequently, this paper provides guidelines for identifying PSS that are effective in terms of value creation. First, the product and service elements of the PSS should have sufficient autonomous value to be sold separately on the market. Secondly, they should come from different quadrants of the 2×2 matrix. Lastly, the combination of product and service elements should create synergy. Through a survey among product and service developers and an experimental auction among customers we validate our ideas.